Effectiveness of early heparin therapy on outcomes in critically ill patients with sepsis-induced coagulopathy - Huang, Jia-Jia; Zou, Zhi-Ye; Zhou, Zhi-Peng; Liu, Yan; Yang, Zhen-Jia; Zhang, Jing-Jing; Luan, Ying-Yi; Yao, Yong-Ming; Wu, Ming (Frontiers in Pharmacology, 2023)
Background This study aimed to investigate whether prophylactic heparin administration provides a survival advantage for patients with sepsis-induced coagulopathy (SIC). Methods Patients with SIC were identified from the Medical Information Mart for Intensive Care-IV database. The primary endpoint was ICU mortality, the secondary outcomes were 7-day, 14-day, and 28-day mortality as well as hospital mortality. Propensity score matching (PSM) the marginal structural Cox model (MSCM) and E-value analysis were used to account for baseline differences, time-varying confounding and unmeasured confounders. Results A total of 6498 septic patients with SIC were enrolled in the study, with 1284 in the heparin group and 5124 in the non-heparin group. There was no significant effect on ICU mortality in the overall population (hazard ratio [HR]0.89, 95% confidence interval [CI] 0.70-1.12). Interestingly, MSCM had a significant effect on ICU mortality in the overall population (HR 0.77, 95% CI 0.60-0.98). Stratification analysis with the MSCM showed that prophylactic heparin administration was associated with decreased ICU mortality only among patients with an SIC score of 4 (HR 0.63, 95% CI 0.45-0.89). Similar results were replicated with PSM only for patients with a SIC score of 4 (ICU mortality HR 0.68, 95% CI 0.49-0.95; 7-day mortality HR 0.59, 95% CI 0.36-0.98; 14-day mortality HR 0.66, 95% CI 0.44-0.98; hospital mortality HR 0.77, 95% CI 0.58-1.03; 28-day mortality HR 0.77, 95% CI 0.54-1.10). Conclusions: Prophylactic heparin to patients with a SIC score of 4 appears to be associated with improved survival outcomes, including ICU mortality, 7-day mortality and 14-day mortality.